Combinatory transplantation of mesenchymal stem cells with flavonoid small molecule in acellular nerve graft promotes sciatic nerve regeneration. (December 2020) - Li, Wen-yuan; Jia, Hua; Wang, Zhen-Dong; Zhai, Feng-guo; Sun, Guang-da; Ma, Duo; Liu, Gui-Bo; Li, Chun-Mei; Wang, Ying
Previous animal studies have demonstrated that the flavonoid small-molecule TrkB agonist, 7, 8-dihydroxyflavone (DHF), promotes axon regeneration in transected peripheral nerves. In the present study, we investigated the combined effects of 7, 8-DHF treatment and bone marrow-derived stem/stromal cells (BMSCs) engraftment into acellular nerve allografts (ANAs) and explore relevant mechanisms that may be involved. Our results show that TrkB and downstream ERK1/2 phosphorylation are increased upon 7, 8-DHF treatment compared to the negative control group. Also, 7, 8-DHF promotes proliferation, survival, and Schwann-like cell differentiation of BMSCs in vitro. While selective ERK1/2 inhibitor U0126 suppressed the effect of upregulation of ERK1/2 phosphorylation and decreased cell proliferation, survival, and Schwann-like cell differentiation partially induced by 7, 8-DHF. In vivo, 7, 8-DHF promotes survival of transplanted BMSCs and upregulates axonal growth and myelination in regenerating ANAs. 7, 8-DHF+BMSCs also improved motor endplate density of target musculature. These benefits were associated with increased motor functional recovery. 7, 8-DHF+BMSCs significantly upregulated TrkB and ERK1/2 phosphorylation expression in regenerating ANA, and increased TrkB expression in the lumbar spinal cord. The mechanism of 7, 8-DHF action may be related to its ability to upregulate TrkB signaling, and downstream activation of survival signaling molecules ERK1/2 in the regenerating ANAs and spinal cord and improved survival of transplanted BMSCs. This study provides novel foundational data connecting the benefits of 7, 8-DHF treatment in neural injury and repair to BMSCs biology and function and demonstrates a potential combination approach for the treatment of injured peripheral nerve via nerve graft transplant.